1972
DOI: 10.1139/v72-336
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Organophosphorus Derivatives. Part I. Nuclear Magnetic Resonance Studies of the 2-Oxo-1,3,2-dioxaphosphorinane System

Abstract: The n.m.r. spectra of a series of simple derivatives of the 2-0x0-l,3,2-dioxaphosphorinane system are discussed in terms of the favored conformations of the derivatives and the stereospecific dependencies of vicinal 31P-O-C-' H couplings. Attention is drawn to a type of "deceptively-simple" ABX spectrum which is commonly found for the n.m.r. spectra of substances containing one or more heteronuclear species.Les spectres r.m.n. d'une strie de dtrivts simples du systtme 2-0x0-l,3,2-dioxaphosphorinane sont discut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
3

Year Published

1977
1977
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…4). This observation suggests that in the general "Karplus-like" correlation equation, the importance of the B factor (operating on the cos 0 term) decreases with the electronegativity of the phosphorus substituents: similar observations can be deduced from a comparison of the 3Jpocl, values of phosphonates and phosphates (27), as well as from a comparison of the 'JPmC values of phosphonates and phosphine oxides ( 17).…”
Section: Spectroscopic Properties Of 312-phosphorus-bearingmentioning
confidence: 57%
“…4). This observation suggests that in the general "Karplus-like" correlation equation, the importance of the B factor (operating on the cos 0 term) decreases with the electronegativity of the phosphorus substituents: similar observations can be deduced from a comparison of the 3Jpocl, values of phosphonates and phosphates (27), as well as from a comparison of the 'JPmC values of phosphonates and phosphine oxides ( 17).…”
Section: Spectroscopic Properties Of 312-phosphorus-bearingmentioning
confidence: 57%
“…Of course glycosidic angle values closer to zero for 5'-GMP/L~"' at pH 1.2 (Table 4) range 'JpilJ. coupling constant in the complex when compared to the value of 1.2 Hz for the free ligand at the same pH (32).…”
Section: H{h}noe Valuesmentioning
confidence: 84%
“…Theoretical and experimental studies of 'JHkI and 'JPl, coupling constants through saturated bonds (32,33) have shown that they have maximum values for a planar W atom arrangement. These studies are applicable to 5'-GMP at low pH (pH < 2) as, when the guanine base is saturated, the bond order C,-N, is about one.…”
Section: H{h}noe Valuesmentioning
confidence: 99%
“…Similarly, a convenient 3~p O C H VS. OpH correlation can be easily deduced from many previous works (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26), including studies of cyclic phosphates. This relationship has been shown to be susceptible to the coordination number of the phosphorus atom (27), ring-strain, and bond angle distortions (13b, 15,28).…”
mentioning
confidence: 99%
“…However, the l~p o C H VS. epH relationship proposed by Lee and Sarma (13a) (eq. [2]) has been used extensively and successfully for conformational assignment of various dioxaphosphorinane rings previously studied, including conformationally "free" six-membered rings (19,20), sixmembered phosphate rings fused cis to five-membered sugar rings (13b, 15), and similar trans-fused bicyclic systems (13a). The relevant function is:…”
mentioning
confidence: 99%